Evaluation Of The Performance Of A Conceptual Pipe Heater With The Addition Of A Vortex Generator To Overcome Ice Formation - Audrey Ginnifer (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Horizontal stabilizer is component crucial on responsible aircraft​ answer control attitude the flight . Disturbance on the horizontal stabilizer you can result disappearance stability aircraft . The anti-icing system on the horizontal stabilizer is functioning For prevent contamination on the leading edge of the current wing aircraft fly . However , an anti-icing system is in place need energy electricity additional , which can be add burden Work machine , though There is energy calories that haven't yet utilized in a way optimal.In study this , done analysis to influence Variation of vortex generator on heater. Results study show that the pressure drop for twisted is 16.70 Pa and wire coil is 14.38 Pa, so twisted has a higher pressure drop Good rather than wire coil. Besides that is , displacement heat the twisted reaches 70.32 Watts and the wire coil reaches 70.11 Watts, so the twisted has displacement more calories​ Good . This matter caused by high friction factor value on twisted, produces low Reynolds number . Low Reynolds number result speed Genre small air , so​ air longer contact​ with heater , increase displacement hot in a way effective .